2019
DOI: 10.48550/arxiv.1908.00082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A refinement of Khovanov homology

Andrew Lobb,
Liam Watson

Abstract: We refine Khovanov homology in the presence of an involution on the link. This refinement takes the form of a triply-graded theory, arising from a pair of filtrations. We focus primarily on strongly invertible knots and show, for instance, that this refinement is able to detect mutation.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…For example, a prominent open problem was resolved when Piccirillo showed that the Conway knot is not slice, using the s-invariant [44] defined by Rasmussen from the spectral sequence from Khovanov homology to Lee homology. Lobb-Watson's [34] filtered invariant is able to detect mutants in the presence of an involution. In a different direction, one may also consider generalized mutations along genus 2 surfaces from which (Conway) mutation may be recovered.…”
Section: 2mentioning
confidence: 99%
“…For example, a prominent open problem was resolved when Piccirillo showed that the Conway knot is not slice, using the s-invariant [44] defined by Rasmussen from the spectral sequence from Khovanov homology to Lee homology. Lobb-Watson's [34] filtered invariant is able to detect mutants in the presence of an involution. In a different direction, one may also consider generalized mutations along genus 2 surfaces from which (Conway) mutation may be recovered.…”
Section: 2mentioning
confidence: 99%